Fenomena Cancel Culture Di Platfrom Instagram: Analisis Pembungkaman Simbolik Terhadap Gus Miftah - Siti Nabila Ria; Eceh Trisna Ayuh (STAI Bumi Silampari, 2025)
This research aims to understand how cancel culture functions as a mechanism for symbolic silencing of public figures in the digital space, focusing on the Gus Miftah case in the dynamics of public opinion on Indonesian social media. Elisabeth Noelle-Neumann's Spiral of Silence theory is used to explain the tendency of individuals to choose silence when their opinions conflict with the majority opinion, as well as how the dominance of certain opinions creates a repressive social climate against diversity of views. The method used is a descriptive qualitative approach with data collection techniques in the form of observation of social media content, especially Instagram, literature studies, and digital documentation of public narratives that developed during the viral period of the Gus Miftah case. The results showed that cancel culture against Gus Miftah was not only a spontaneous criticism, but also an organized process that formed collective social pressure. When negative opinions dominate, supporters or parties with different views tend to remain silent, showing the spiral of silence mechanism in action. As a result, symbolic silencing occurs, where public figures lose legitimacy without space for open dialogue. This research emphasizes the importance of maintaining diversity of opinion in the digital space so that freedom of expression is preserved.